Theoretical background for the bionic substantiation of parameters of the stubble cultivator working bodies - L. F. Babitsky; I. V. Sobolevsky; V. A. Kuklin (Аграрная наука Евро-Северо-Востока)
In the southern regions of Russia, the technology of cultivation of grain crops in the variant of partial sowing has been widely used. In this regard, it became necessary to create effective working bodies of a stubble cultivator that would have fundamentally new resource-saving ways of influencing the area under cultivating and meet the requirements of modern advanced technologies. The shapes of the working bodies surfaces of the cultivators were improved taking into account the mechanic-bionic approach. The main parameters of the toothed cutting surface were determined by the method of bionic comparisons, with a scarab beetle as a bionic prototype. Use of the serrated shape of the cutting edge is consistent with the bionic principle of multi-contact exposure and leads to the fact that the tops of the teeth become stress concentrators and, with a significantly smaller indentation force, cause soil destruction processes, which reduces the energy costs of cutting the soil layer. The optimal curvilinear shape of the working surface made in the form of a logarithmic spiral, is characterized by a constant value of the angle between the normal and the radius vector, and the value of this angle, equal to the angle of internal friction of the soil φ2, will ensure the sliding of the soil and plant residues with minimal energy consumption. The number (n = 4), height (h = 5...7 mm) and tooth placement step (S = 10...12 mm) of the bit tip of the stubble cultivator are analytically justified. The shape of the profile of the working surface of the stubble cultivator bit in the form of a logarithmic spiral with a variable angle of crumbling is proposed. The studies were conducted in the period from September to October 2018 in the soil channel of the research Laboratory of Bionic Agroengineering of the Department of Mechanization and Technical Service in Agro-Industrial Complex. They have shown the decrease in the traction resistance of the proposed working body of the stubble cultivator by 16.5% in comparison with the traction resistance of the serial sample.